If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -18 = 94 Reorder the terms: -18 + 7x = 94 Solving -18 + 7x = 94 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 7x = 94 + 18 Combine like terms: -18 + 18 = 0 0 + 7x = 94 + 18 7x = 94 + 18 Combine like terms: 94 + 18 = 112 7x = 112 Divide each side by '7'. x = 16 Simplifying x = 16
| x+20=-40 | | [7(n+5)-16]+[3(n-3)+4]= | | x+11=-10 | | (2)3+3y=6 | | 4x^3/(5x^3+5) | | 30+x=69 | | 1.6m=-70 | | 1.6m=-77 | | 4v-5=-1 | | x+17=-17 | | -14=6+v/4 | | 3/4a=6 | | 4u-8=16 | | x+32=-12 | | 4/(5y-25)+1=-8/(y-5) | | 22+x=-8 | | 4/(5y-25)+1 | | 4xy+x=10 | | xy=8 | | 0.85m=-24 | | (5+u)(3u-2)=0 | | 7x^2+11xy-6y^2= | | x^2-24xy+63y^2= | | x^2+24xy+63y^2= | | (5x+8)/7=6 | | 19=7x-39 | | N+8=3n+20 | | gt=5g+5z | | 3(-6x+4/2+3)-5=25 | | 3(-6x+4+3)-5=25 | | 6x-8=.33333333(18x+24) | | (6x2+43x+39)/x+6 |